IMPLEMENTATION OF THE GUIDED INQUIRY LEARNING MODEL TO IMPROVE SCIENTIFIC REASONING ON VIRUS MATERIAL FOR GRADE X STUDENTS AT SMA NEGERI 7 PEKANBARU - Indah Ade Lestari; Evi Suryawati; Fitra Suzanti (Yayasan Amanah Nur Aman, 2026)
Twenty-first-century learning requires students to possess higher-order thinking skills, one of which is scientific reasoning. The low level of students’ scientific reasoning is caused by learning processes that are still teacher-centered, resulting in students being less active in developing scientific thinking skills. This study aimed to determine the improvement of students’ scientific reasoning abilities through the implementation of the guided inquiry learning model. This study employed a quasi-experimental method with a pretest–posttest control group design. The research samples were classes X.7 and X.8, selected using purposive sampling techniques. The guided inquiry learning model supported by PowerPoint instructional media was applied in the experimental class during the learning process, while the control class used the discovery learning model. The research instruments consisted of a scientific reasoning test and observation sheets. The results showed that the average posttest score of the experimental class reached 88.75%, categorized as scientific reasoning, while the control class reached 69.19%, categorized as moderate scientific reasoning. The N-gain test results indicated that the level of scientific reasoning in the experimental class was in the effective category (0.74), higher than that of the control class (0.60). The data were analyzed using an independent samples t-test, yielding a significance value (2-tailed) of 0.000 < 0.05. Thus, the implementation of the guided inquiry learning model was proven to have a significant effect on improving students’ scientific reasoning on virus material.